Mindfulness-based stress reduction intervention during pregnancy changes maternal brain - Yvan Gomez; Ayako Nakaki; Allegra Conti; Sara Castro-Barquero; Benedetta Gambosi; Irene Casas; Mariona Genero; Lina Youssef; Leticia Benitez; Noelia Encabo; Rosa Casas; Andrés Martín-Asuero; et al. (Scientific Reports)
Abstract Our aim is to evaluate the effect of a structured stress reduction intervention based on mindfulness during pregnancy on the maternal brain. We report a secondary analysis of IMPACT BCN, a randomized clinical trial including pregnant women randomly allocated to 8-week Mindfulness-Based Stress Reduction (n = 41) or usual care (without any intervention, n = 35). Maternal magnetic resonance (MR) was performed in the third trimester, cluster-wise analysis was used to assess cortical morphometric differences, and proton magnetic resonance spectroscopy (1H-MRS) to evaluate the metabolic characteristics. Mindfulness status was evaluated using the Five Facet Mindfulness Questionnaire (FFMQ). Results showed that participants from Stress reduction group had significantly larger surface areas in the right superior frontal region as compared to the Usual care group (90%CI: 0.023–0.029, p = 0.03). The1H-MRS revealed that Stress reduction group participants, had higher concentrations of myo-inositol (adjusted mean difference D 0.37 mol/L, 95%CI 0.05–0.69) as compared to Usual care. Participants who had high mindfulness on FFMQ facets of non-judgmental (D 358.5 mm2, 95%CI 53.5-663.6) and non-reactivity (D 362.3 mm2, 95%CI 18.8-705.7) had larger right superior frontal area. In conclusion, Mindfulness-Based Stress Reduction program during pregnancy has a significant effect on maternal brain structure and is associated with metabolite concentration changes.